2020
DOI: 10.1002/hbm.25326
|View full text |Cite
|
Sign up to set email alerts
|

FreeSurfer‐based segmentation of hippocampal subfields: A review of methods and applications, with a novel quality control procedure for ENIGMA studies and other collaborative efforts

Abstract: Structural hippocampal abnormalities are common in many neurological and psychiatric disorders, and variation in hippocampal measures is related to cognitive performance and other complex phenotypes such as stress sensitivity. Hippocampal subregions are increasingly studied, as automated algorithms have become available for mapping and volume quantification. In the context of the Enhancing Neuro Imaging Genetics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 267 publications
1
58
0
Order By: Relevance
“…In FreeSurfer v.5.3, the atlas is built in vivo scans at 0.38 × 0.38 × 0.80 mm 3 resolution (without manual delineation), yielding voxels larger than the ex vivo protocol (version 6.0). 16 Moreover, 2 studies used MAGeT-Brain (Multiple Automatically-GEnerated Templates). 17,18 In MAGeT, hippocampal subfield segmentation is driven by propagating atlas segmentations (optimal number of atlases, 9) to a template library, formed from a subset of target images (with several types of image acquisition and disease populations), via transformations estimated by nonlinear image registration.…”
Section: Segmentation Softwarementioning
confidence: 99%
“…In FreeSurfer v.5.3, the atlas is built in vivo scans at 0.38 × 0.38 × 0.80 mm 3 resolution (without manual delineation), yielding voxels larger than the ex vivo protocol (version 6.0). 16 Moreover, 2 studies used MAGeT-Brain (Multiple Automatically-GEnerated Templates). 17,18 In MAGeT, hippocampal subfield segmentation is driven by propagating atlas segmentations (optimal number of atlases, 9) to a template library, formed from a subset of target images (with several types of image acquisition and disease populations), via transformations estimated by nonlinear image registration.…”
Section: Segmentation Softwarementioning
confidence: 99%
“…Several papers in this Special Issue focus on technical challenges in harmonizing brain data from different sources worldwide. These challenges were addressed by developing harmonized protocols to analyze specific brain measures, such as hippocampal subfields (Sämann et al, 2020). As many disorders studied by ENIGMA have found abnormalities in the hippocampus, Sämann et al (2020) offer a comprehensive review of approaches and methods used to study hippocampal subfields in clinical populations, offering a finer-grained analysis of hippocampal structure.…”
Section: Methods For Data Integration and Technical Issues In Harmonizing Brain Datamentioning
confidence: 99%
“…These challenges were addressed by developing harmonized protocols to analyze specific brain measures, such as hippocampal subfields (Sämann et al, 2020). As many disorders studied by ENIGMA have found abnormalities in the hippocampus, Sämann et al (2020) offer a comprehensive review of approaches and methods used to study hippocampal subfields in clinical populations, offering a finer-grained analysis of hippocampal structure. Based on experience applying subfield analysis to diverse data worldwide, they present in-depth guidelines for segmentation and quality control of subfield measures as part of an illustrated and validated protocol for the quality control and analysis of subfield data-one that is widely used across ENIGMA.…”
Section: Methods For Data Integration and Technical Issues In Harmonizing Brain Datamentioning
confidence: 99%
“…Volume measurements of hippocampal s underwent a correction process using the estimated total intracranial volum [17,18]. We carefully inspected the automatic hippocampal subfield segmentatio of all participants on axial, sagittal, coronal images referring the quality control suggested by Samman et al, and confirmed that the segmentations were pe properly [19]. The white matter connectivity of the hippocampus was acquired based on DT DSI studio [20].…”
Section: Image Analysismentioning
confidence: 99%